The resisters : [large type] a novel - Jen, Gish (Thorndike press large print Bill's bookshelf, 2020)
"The time: not so long from now. The place: AutoAmerica. The land: half under water. The Internet: one part artificial intelligence, one part surveillance technology, and oddly human--even funny. The people: Divided. The angel-fair "Netted" have jobs, and literally occupy the high ground. The "Surplus" live on swampland if they're lucky, on water if they're not. The story: To a Surplus couple--he once a professor, she still a lawyer--is born a Blasian girl with a golden arm. At two, Gwen is hurling her stuffed animals from the crib; by ten, she can hit whatever target she likes. Her teens find her happily playing in an underground baseball league. When AutoAmerica rejoins the Olympics, though--with a special eye on beating ChinRussia--Gwen attracts interest. Soon she finds herself playing ball with the Netted even as her mother challenges the very foundations of this divided society. A moving and important story of an America that seems ever more possible, The Resisters is also the story of one family struggling to maintain its humanity and normalcy in circumstances that threaten their every value--as well as their very existence. Extraordinary and ordinary, charming and electrifying, this is Gish Jen at her most irresistible"--